Safeguarding the Unity: The History of the Interpretation of נִגְלוּ in Genesis 35:7. (27th March 2018) - Oseka, Matthew
Abstract : The present paper examines the classic Jewish exposition of the plural grammatical form related to the Divine in Genesis 35:7. It is situated against Christian exegesis developed in antiquity, the Middle Ages, and the Reformation. The Jewish exegetical tradition offered various interpretations of the plural form of נִגְלוּ —which were consistent with the concept of the absolute oneness of the Godhead (fundamental to the Tanakh), and which were rooted in the literary context of Genesis 35:7, and attentive to the grammatical and lexical features of אלוהים . The plural form in Genesis 35:7 was not detected by either the church fathers or by mainstream Christian exegesis during the Middle Ages. Anti-Jewish medieval literature began adducing Genesis 35:7, among the other passages of this kind, as proof of the presence of the trinitarian idea within the Hebrew Bible. This approach was continued and amplified by Martin Luther in contradistinction to other Reformation exegetes who, generally speaking, preferred to appeal to verses such as Genesis 1:26 or Genesis 3:22 in support of their claims.